3D printing porous special-shaped high-entropy alloy component

By 3D printing of porous, unusually shaped high-entropy alloy components, combining high-entropy alloys and calcium hydroxyphosphate, the problem of mismatch in the body of existing metal alloys is solved, and the stability, corrosion resistance and biocompatibility of biomaterials are improved, and it is suitable for hard tissue repair and drug sustained release.

CN119609161APending Publication Date: 2025-03-14安徽恒利增材制造科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411586553.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing metal alloys are corroded or worn in the body due to chemical reactions, resulting in the degradation of the implant performance, and their elastic modulus does not match the human skeleton, affecting biomechanical compatibility.

Method used

Porous and shaped high-entropy alloy components are prepared through 3D printing technology, combining high-entropy alloys and calcium hydroxyphosphate to optimize the electronic structure and microstructure of the material. Laser 3D printing and gel-sol process are used to prepare composite biological materials with suitable pore structures.

Benefits of technology

It has achieved improved stability, corrosion resistance and biocompatibility of biomaterials, provided better mechanical support, is suitable for hard tissue repair, and promotes drug sustained release and cell growth through pore structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119609161A_ABST
    Figure CN119609161A_ABST
Patent Text Reader

Abstract

The invention relates to the field of high-entropy alloys, in particular to a 3D printing porous special-shaped high-entropy alloy component which comprises, by weight, 35%-55% of high-entropy alloy and 43%-65% of hydroxyl calcium phosphate. The 3D printing porous special-shaped high-entropy alloy component has the following beneficial effects that the high-entropy alloy has high hardness, good fatigue resistance and excellent corrosion resistance, and the high-entropy alloy is high in mechanical strength, high in mechanical strength and high in mechanical strength; after being combined with hydroxyapatite, the composite biological material can provide better mechanical support while keeping biocompatibility, is suitable for repairing hard tissues with large bearing capacity, and ensures good and uniform interface combination between hydroxyapatite and the high-entropy alloy by realizing the pore structure of the composite material; therefore, damage to human bodies caused by factors such as cracks and phase separation is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a 3D printed porous special-shaped high-entropy alloy component, belonging to the field of high-entropy alloys. Background Art

[0002] Key metal alloys such as titanium alloys and cobalt-chromium alloys are widely used in medical devices such as artificial joints, bone implants and dental implants due to their excellent biocompatibility and mechanical properties. Metal materials may corrode due to chemical reactions in the body, or wear when in contact with bones or other tissues. These phenomena may lead to a decrease in implant performance and even require secondary surgery. Therefore, high hardness can reduce the possibility of "particle disease" when working as a load-bearing implant material in a physiological environment. At the same time, human bones have a specific elastic modulus, so the elastic modulus of biomedical metal materials should be as close to that of human bones as possible to achieve better biomechanical compatibility and reduce stress shielding effects, which is crucial for the compatibility and long-term stability of materials with human bones and soft tissues. A lower elastic modulus helps promote bone integration, reduce the elastic difference between implants and bones, and reduce stress shielding effects, thereby promoting the growth and integration of bone tissue. The elastic modulus of most human bone tissues ranges from 1 to 30 GPa. However, the elastic modulus of pure titanium is about 110GPa. Although its elastic modulus is closer to that of human bones than other metals and alloys, the mismatch with the modulus of bone tissue will still greatly affect its performance. Summary of the invention

[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a 3D printed porous special-shaped high-entropy alloy component to solve the problems raised in the above background technology.

[0004] In order to achieve the above-mentioned purpose, the present invention is implemented through the following technical scheme: 3D printing porous special-shaped high-entropy alloy components, including high-entropy alloy and hydroxy calcium phosphate, by weight: high-entropy alloy is 35-55%, and hydroxy calcium phosphate is 43-65%.

[0005] A method for preparing a 3D printed porous special-shaped high-entropy alloy component comprises the following steps:

[0006] Step 1: Identify the key metal elements in the alloy;

[0007] Step 2: Preparation of high entropy materials;

[0008] Step 3: Preparation of composite materials;

[0009] Step 4: Laser 3D Printing.

[0010] Specifically, in step 1, the key metal elements in the alloy are titanium, niobium, tantalum, chromium and hafnium. The basic principles of quantum mechanics and solid-state physics are used to calculate the electronic structure of the alloy, the total energy, electronic state density, band structure, etc. of the alloy, and a mechanical alloying method is used to synthesize the designed alloy. A transmission electron microscope and a scanning electron microscope are used to observe the microstructure of the alloy, and tensile tests, compression tests and hardness tests are performed to evaluate the mechanical properties of the alloy.

[0011] Specifically, in step 2, TiO2, ZrO2, HfO2, Nb2O5, Ta2O5 and B4C are used as raw materials, and a boron carbon thermal reduction method is adopted to prepare powders. The reaction temperature is 2050°C and the insulation time is 15 minutes to achieve the synthesis of single-phase high entropy boride powders. The average particle size of the powder is about 431nm. The oxygen impurity content of the powder is effectively controlled by the method of excessive B4C raw material, and finally the effective preparation of high-purity, single-phase nanopowders is achieved.

[0012] Specifically, in step 3, a sol-gel method is used to prepare a hydroxycalcium phosphate / high entropy alloy composite material, using Ca(NO3)2·4H2O and P2O5 as raw materials, adjusting the precursor concentration to 0.05-0.2M, preparing a hydroxycalcium phosphate precursor sol, and fully immersing the prepared porous high entropy alloy stent in the hydroxycalcium phosphate precursor solution. By adjusting the pH value of the solution, the pH value range is 2-4, and the reaction temperature is controlled to 400-800°C, the precursor sol is converted into a hydroxycalcium phosphate coating, and X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques are used to evaluate the coating uniformity and integrity of hydroxycalcium phosphate. The composite material is immersed in a simulated body fluid of a phosphate buffer solution at 37°C and pH 7.4, and its mass loss and surface morphology changes are tested regularly, and the regular time is 1 day, 7 days or 30 days, and an electrochemical impedance spectroscopy test is performed in the simulated body fluid, and the frequency range is set from 10 -2 Hz to 1 5 Hz, comprehensively evaluate the stability, corrosion resistance and biocompatibility of composite biomaterials.

[0013] Specifically, in step 4, the laser power, scanning speed and layer thickness of laser 3D printing are optimized. The laser power starts from 50W and gradually increases to 200W, increasing by 10W each time. The scanning speed range is set to 0.1mm / s-10mm / s, and the layer thickness setting range is 0.05mm-0.5mm. The printing path mode is changed in a straight line, spiral or zigzag shape. A post-processing technology optimization experiment is carried out. The heat treatment temperature range is 500-1000°C, the insulation time is 1-10h, and the porosity is controlled in the range of 40% to 60%. The samples are then subjected to compression test, three-point bending test and fatigue test.

[0014] Beneficial effects of the present invention:

[0015] The pore structure in biomaterials not only provides cells with the necessary attachment and growth space, but also promotes the interaction between cells and the material surface. Appropriate pore size and distribution can effectively promote cell spreading, proliferation and differentiation. In addition, the pore structure can also be used as a drug carrier to achieve sustained and controlled release of drugs, thereby improving the efficacy and safety of drugs. The pore structure can also reduce the density of biomaterials and reduce weight while maintaining certain mechanical properties.

[0016] Combined with 3D printing additive manufacturing technology, the effective preparation of porous high-entropy alloy scaffolds is achieved. The gel-sol process is used to achieve in-situ deposition of hydroxyapatite on the surface of porous high-entropy alloys. The growth and microstructure regulation mechanism of hydroxyapatite is elucidated, and the effective preparation of hydroxyapatite / high-entropy alloy porous composite biomaterials is achieved. Ultimately, the overall improvement of implantable biocomposite materials in terms of stability, corrosion resistance, drug release mechanism and antibacterial properties is achieved.

[0017] High entropy alloys have high hardness, good fatigue resistance and excellent corrosion resistance. When combined with hydroxyapatite, the composite biomaterial can provide better mechanical support while maintaining biocompatibility. It is suitable for the repair of hard tissues with heavy loads. By realizing the pore structure of the composite material, a good and uniform interface bonding between hydroxyapatite and high entropy alloy is ensured, thereby avoiding damage to the human body caused by factors such as cracks and phase separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0019] Figure 1 The microstructure of the high entropy alloy stent;

[0020] Figure 2 Prepare process diagrams for high entropy materials;

[0021] Figure 3 The microstructure of Ti-based high entropy alloy; DETAILED DESCRIPTION

[0022] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0023] See also Figures 1 to 3 The present invention provides a technical solution: 3D printing porous special-shaped high-entropy alloy components, including high-entropy alloy and hydroxy calcium phosphate, in which the high-entropy alloy accounts for 35-55% and the hydroxy calcium phosphate accounts for 43-65% by weight.

[0024] A method for preparing a 3D printed porous special-shaped high-entropy alloy component comprises the following steps:

[0025] Step 1: Identify the key metal elements in the alloy;

[0026] Step 2: Preparation of high entropy materials;

[0027] Step 3: Preparation of composite materials;

[0028] Step 4: Laser 3D Printing.

[0029] In step 1, the key metal elements in the alloy are titanium, niobium, tantalum, chromium and hafnium. The electronic structure of the alloy is calculated using the basic principles of quantum mechanics and solid-state physics, and the total energy, electronic state density, band structure, etc. of the alloy are calculated. The designed alloy is synthesized by a mechanical alloying method, and a transmission electron microscope and a scanning electron microscope are used to observe the microstructure of the alloy. Tensile tests, compression tests and hardness tests are performed to evaluate the mechanical properties of the alloy.

[0030] In the step 2, TiO2, ZrO2, HfO2, Nb2O5, Ta2O5 and B4C are used as raw materials, and a boron carbon thermal reduction method is adopted to prepare the powder. The reaction temperature is 2050°C and the insulation time is 15 minutes to achieve the synthesis of single-phase high entropy boride powder. The average particle size of the powder is about 431nm. The oxygen impurity content of the powder is effectively controlled by the method of excessive B4C raw material, and finally the effective preparation of high-purity, single-phase nano powder is achieved.

[0031] In step 3, a sol-gel method is used to prepare a hydroxy calcium phosphate / high entropy alloy composite material, using Ca(NO3)2·4H2O and P2O5 as raw materials, adjusting the precursor concentration to 0.05-0.2M, preparing a hydroxy calcium phosphate precursor sol, and fully immersing the prepared porous high entropy alloy stent in the hydroxy calcium phosphate precursor solution. By adjusting the pH value of the solution, the pH value range is 2-4, and the reaction temperature is controlled to 400-800°C, the precursor sol is converted into a hydroxy calcium phosphate coating, and X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques are used to evaluate the coating uniformity and integrity of hydroxy calcium phosphate. The composite material is immersed in a simulated body fluid of a phosphate buffer solution at 37°C and pH 7.4, and its mass loss and surface morphology changes are tested regularly, the regular time is 1 day, 7 days or 30 days, and an electrochemical impedance spectroscopy test is performed in the simulated body fluid, and the frequency range is set from 10 -2 Hz to 1 5 Hz, comprehensively evaluate the stability, corrosion resistance and biocompatibility of composite biomaterials.

[0032] In step 4, the laser power, scanning speed and layer thickness of laser 3D printing are optimized. The laser power starts from 50W and gradually increases to 200W, increasing by 10W each time. The scanning speed range is set to 0.1mm / s-10mm / s, and the layer thickness setting range is 0.05mm-0.5mm. The printing path mode is changed in a straight line, spiral or zigzag shape. A post-processing technology optimization experiment is carried out. The heat treatment temperature range is 500-1000°C, the insulation time is 1-10h, and the porosity is controlled within the range of 40% to 60%. The samples are then subjected to compression test, three-point bending test and fatigue test.

[0033] The pore structure in biomaterials not only provides cells with the necessary attachment and growth space, but also promotes the interaction between cells and the material surface. Appropriate pore size and distribution can effectively promote cell spreading, proliferation and differentiation. In addition, the pore structure can also be used as a drug carrier to achieve sustained and controlled release of drugs, thereby improving the efficacy and safety of drugs. The pore structure can also reduce the density of biomaterials and reduce weight while maintaining certain mechanical properties.

[0034] Combined with 3D printing additive manufacturing technology, the effective preparation of porous high-entropy alloy scaffolds is achieved. The gel-sol process is used to achieve in-situ deposition of hydroxyapatite on the surface of porous high-entropy alloys. The growth and microstructure regulation mechanism of hydroxyapatite is elucidated, and the effective preparation of hydroxyapatite / high-entropy alloy porous composite biomaterials is achieved. Ultimately, the overall improvement of implantable biocomposite materials in terms of stability, corrosion resistance, drug release mechanism and antibacterial properties is achieved.

[0035] High entropy alloys have high hardness, good fatigue resistance and excellent corrosion resistance. When combined with hydroxyapatite, the composite biomaterial can provide better mechanical support while maintaining biocompatibility. It is suitable for the repair of hard tissues with heavy loads. By realizing the pore structure of the composite material, a good and uniform interface bonding between hydroxyapatite and high entropy alloy is ensured, thereby avoiding damage to the human body caused by factors such as cracks and phase separation.

[0036] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. 3D printed porous special-shaped high entropy alloy components, characterized by The invention comprises a high entropy alloy and hydroxy calcium phosphate, wherein the high entropy alloy accounts for 35-55% and the hydroxy calcium phosphate accounts for 43-65% by weight.

2. The method for preparing a 3D printed porous special-shaped high-entropy alloy component according to claim 1, characterized in that The following steps are involved: Step 1: Identify the key metal elements in the alloy; Step 2: Preparation of high entropy materials; Step 3: Preparation of composite materials; Step 4: Laser 3D Printing.

3. The method for preparing a 3D printed porous special-shaped high-entropy alloy component according to claim 2, characterized in that: In step 1, the key metal elements in the alloy are titanium, niobium, tantalum, chromium and hafnium. The electronic structure of the alloy is calculated using the basic principles of quantum mechanics and solid-state physics, and the total energy, electronic state density, band structure, etc. of the alloy are calculated. The designed alloy is synthesized by a mechanical alloying method, and a transmission electron microscope and a scanning electron microscope are used to observe the microstructure of the alloy. Tensile tests, compression tests and hardness tests are performed to evaluate the mechanical properties of the alloy.

4. The method for preparing a 3D printed porous special-shaped high-entropy alloy component according to claim 2, characterized in that: In the step 2, TiO2, ZrO2, HfO2, Nb2O5, Ta2O5 and B4C are used as raw materials, and a boron carbon thermal reduction method is adopted to prepare the powder. The reaction temperature is 2050°C and the insulation time is 15 minutes to achieve the synthesis of single-phase high entropy boride powder. The average particle size of the powder is about 431nm. The oxygen impurity content of the powder is effectively controlled by the method of excessive B4C raw material, and finally the effective preparation of high-purity, single-phase nano powder is achieved.

5. The method for preparing a 3D printed porous special-shaped high-entropy alloy component according to claim 1, characterized in that: In step 3, a sol-gel method is used to prepare a hydroxy calcium phosphate / high entropy alloy composite material, using Ca(NO3)2·4H2O and P2O5 as raw materials, adjusting the precursor concentration to 0.05-0.2M, preparing a hydroxy calcium phosphate precursor sol, and fully immersing the prepared porous high entropy alloy stent in the hydroxy calcium phosphate precursor solution. By adjusting the pH value of the solution, the pH value range is 2-4, and the reaction temperature is controlled to 400-800°C, the precursor sol is converted into a hydroxy calcium phosphate coating, and X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques are used to evaluate the coating uniformity and integrity of hydroxy calcium phosphate. The composite material is immersed in a simulated body fluid of a phosphate buffer solution at 37°C and pH 7.4, and its mass loss and surface morphology changes are tested regularly, the regular time is 1 day, 7 days or 30 days, and an electrochemical impedance spectroscopy test is performed in the simulated body fluid, and the frequency range is set from 10 -2 Hz to 1 5 Hz, comprehensively evaluate the stability, corrosion resistance and biocompatibility of composite biomaterials.

6. The 3D printed porous special-shaped high-entropy alloy component according to claim 1, characterized in that: In step 4, the laser power, scanning speed and layer thickness of laser 3D printing are optimized. The laser power starts from 50W and gradually increases to 200W, increasing by 10W each time. The scanning speed range is set to 0.1mm / s-10mm / s, and the layer thickness setting range is 0.05mm-0.5mm. The printing path mode is changed in a straight line, spiral or zigzag shape. A post-processing technology optimization experiment is carried out. The heat treatment temperature range is 500-1000°C, the insulation time is 1-10h, and the porosity is controlled within the range of 40% to 60%. The samples are then subjected to compression test, three-point bending test and fatigue test.